Stanford Type B aortic dissection following transradial coronary angiography in a patient with an aberrant right subclavian artery: a case report - Jun Ma; Wei Wang; Hua Yan (Frontiers in Cardiovascular Medicine, 2026)
Aberrant right subclavian artery (ARSA) represents the most prevalent congenital anatomical malformation of the aortic arch. Most affected patients remain asymptomatic, making ARSA prone to misdiagnosis before procedures, which markedly increases the risk of vascular injury during interventional procedures through the right radial artery. We report a 62-year-old woman with coronary artery disease in whom ARSA was not identified preoperatively. During coronary angiography (CAG) performed via right transradial access, iatrogenic dissection of the aberrant right subclavian artery occurred and extended retrogradely to form a Stanford Type B aortic dissection measuring 70 mm in total length, with a 5.6-mm intimal tear at the proximal segment of the ARSA. The patient received conservative management including strict blood pressure control and analgesia after the procedure, and was discharged in improved condition.